(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research is titled, Identity Crisis in the Post-Colonialism Novels, The Novel “Whdaha SHjarat AL-Rumman” as an example. This research is a description about identity crisis in a novel by the Iraqi author (Sinan Antoon) that is regarded as one of the post-colonialism novels. In this research, we have talked about that the author represents the agony, wars, devastation and havoc Iraq went through starting from the outset of the Iraq-Iran war until the emergence of the ISIS. The author, as a critic, has strived for focusing on the atrocities and consequences of war on the Iraqis of all different groups. Concurrently, he has strived for working on the novel text using a scene or making a character as the novel protagonist and the details of showing the different crises of an intellectual individual like social, economic, political and cultural crises. Our research is backed by the theoretical subjects relevant to the post-colonialism approach and the concepts and aspects the approach relies on that are deviation from sticking to a certain identity and the conflict that identity creates with crises aiming to reach stability and keeping the identity of Iraqi individuals. The author has regarded using a new and different language as he has personally lived in the events and has then chosen diaspora due to war and devastation to reach a sort of stability and protection. According to the theory, this situation, once again, results in identity crisis. Finally, we have explained the text using the method of textual analysis and presented some conclusions.